2017
DOI: 10.14295/oh.v23i1.927
|View full text |Cite
|
Sign up to set email alerts
|

Sensory analysis and postharvest of potted gerbera based on fertilization

Abstract: The cultivation of gerberas as cut flowers has been broadly studied. With the purpose of assess the production and visual quality of potted gerberas conducted with different fertilizations, the experiment was performed in a greenhouse located at UNIOESTE -Campus of Cascavel -Parana -Brazil. The experimental design was done in randomized blocks with four repetitions and five treatments. The treatments were defined based on the fertilization source: mineral (NPK) or organic. The organic fertilizations were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…As for the efficiency of P use, some plants have a greater capacity to redistribute and reuse nutrients from an older, senescent organ for biomass production (ROZANE et al, 2007). Santos et al (2017) observed that organic fertilization with industrial waste did not increase shoot and inflorescence diameters of potted gerbera, in relation to mineral fertilization. Ludwig et al (2013) found that P was the fifth macronutrient most required by the Red potted gerbera, and the accumulated amount of nutrient in the plant shoot was 42 mg plant -1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As for the efficiency of P use, some plants have a greater capacity to redistribute and reuse nutrients from an older, senescent organ for biomass production (ROZANE et al, 2007). Santos et al (2017) observed that organic fertilization with industrial waste did not increase shoot and inflorescence diameters of potted gerbera, in relation to mineral fertilization. Ludwig et al (2013) found that P was the fifth macronutrient most required by the Red potted gerbera, and the accumulated amount of nutrient in the plant shoot was 42 mg plant -1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to these authors, very tall and thin stems in potted gerbera may not have suffi cient support and cause tipping. Santos et al (2017) obtained a stem length for potted gerbera ranging from 17.6 to 23.3 cm, in an experiment in which organic fertilization from agribusiness waste and mineral fertilization were used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the end of the composting process, organic composts with high electrical conductivity (EC) of 5.63; 8.29; 3.63; and 5.46 dS m -1 , for treatments 2, 3, 4, and 5, respectively, were generated, limiting their use as substrates for the production of potted gerbera. Thus, the dilution of organic composts in water presents a way of supplying the nutritional needs of gerbera's culture, as well as adjusts the EC (Santos et al, 2017). Then, a dilution of the organic compost in order to use only the liquid fraction of fertigation for culture was performed.…”
Section: Methodsmentioning
confidence: 99%